Zolbetuximab for Claudin18.2-positive gastric or gastroesophageal junction cancer - Yohei Kubota; Kohei Shitara (Therapeutic Advances in Medical Oncology, 2024)
Claudins (CLDNs) are a family of major membrane proteins that form components of tight junctions. In normal tissues, CLDNs seal the intercellular space in the epithelial sheets to regulate tissue permeability, paracellular transport, and signal transduction. Claudin18.2 (CLDN18.2), a member of the CLDN family, is expressed specifically in gastric mucosal cells in normal tissue, and its expression is often retained in gastric cancer cells. CLDN18.2 is ectopically expressed in many cancers other than gastric cancer such as esophageal cancer, pancreatic cancer, biliary tract cancer, non-small-cell lung cancer, and ovarian cancer. Structurally, CLDN18.2 is localized on the apical side of the cell membrane and has extracellular loops capable of binding monoclonal antibodies. Upon malignant transformation, CLDN18.2 is exposed to the cell surface of the whole membrane, which enables the binding of monoclonal antibodies. Based on these characteristics, CLDN18.2 was considered to be optimal for target therapy, and zolbetuximab was developed which is a first-in-class chimeric immunoglobulin G1 monoclonal antibody highly specific for CLDN18.2. It binds to CLDN18.2 on the tumor cell surface and stimulates cellular and soluble immune effectors that activate antibody-dependent cytotoxicity and complement-dependent cytotoxicity. Recently, zolbetuximab combined with chemotherapy demonstrated a survival benefit in patients with CLDN18.2-positive and HER-2-negative gastric or gastroesophageal junction cancers in the global phase III SPOTLIGHT and GLOW trials. From these clinically meaningful results, CLDN18.2-targeting therapy including zolbetuximab has attracted a lot of attention. In this review, we summarize the clinical implications of CLDN18.2-positive gastric or GEJ cancer, and CLDN18.2-targeting therapy, mainly for zolbetuximab.